Lithium-ion battery 2nd life used as a stationary energy storage system: Ageing and economic analysis in two real cases. (1st November 2020) - Rallo, H.; Canals Casals, L.; De La Torre, D.; Reinhardt, R.; Marchante, C.; Amante, B.
Abstract: Electric vehicles (EVs) are considered a viable alternative to internal combustion engine vehicles (ICEVs) and as a result of recent advances in battery technologies, sales are increasing year by year. However, recycling these batteries at the end of their useful life in the car can be a problem because they contain materials that can harm human health and the environment. Thus, car manufacturers consider that when those batteries have finished their first life in an EV, they still contain enough energy and capacity to be used in a stationary energy storage systems (SESSs), significantly contributing towards an increased sustainable transport sector in the future. This study focuses the analysis on the viability of a SESS installation, considering battery ageing from an economic perspective in two different real scenarios in Spain. This study simulates the electricity bill cost with and without SESS and calculates the annual savings accordingly. Following, the return on investment (ROI) of installing a SESS is calculated. Afterwards the lifetime of the batteries is calculated in order to compare it with the ROI and to decide if the installation of a SESS is advisable from an economic point of view. Major results indicate that any feasibility study of installing a SESS must be studied from an economic and battery ageing point of view. Highlights: Battery second life can reduce final EV selling price. Second life EV batteries still have enough energy & capacity to be used as a SESS. The current price of battery second life does not guarantee economic viability of the SESS. Energy arbitrage is the most profitable strategy to be used in a SESS. The battery ageing determines the economic viability of any SESS.